The Motor Industry: an economic survey - Rhys, D. G. (England, London Butterworth, 1972)
The book illustrates and explains the development and structure of the motor industry and how the industry fits in with the economist's theory of the firm.
includes index
occ 17/01/2019
Loans
Keywords: Motor vehicles; Automobile industry and trade